Implementation of Game-Based Thematic Science Approach in Developing Early Childhood Cognitive Capabilities - Ayu Suryaningsih; Ni Luh Rimpiati (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This study aims to improve the cognitive abilities of early childhood through a game-based science thematic approach. The study was conducted on Pradnyandari III TK Kerobokan group B (aged 5-6 years) children in semester 2 of the school year 2017/2018. This type of research is classroom action research with a procedure consisting of four stages, namely: planning, action taking, development (observation), and reflection. This research was conducted in two cycles. The data collection method used is the observation method. Data on increasing children's cognitive abilities were analyzed descriptively. The results presented in the implementation of this study were an increase in cognitive abilities of early childhood, after following the learning process with a game-based science thematic approach. In the initial observation, the number of completeness was 37.5%. The increase incompleteness of children's cognitive abilities occurred in the first cycle, to 70.83% and again increased in the second cycle to 91.67%. So it can be concluded that the application of a thematic-based science thematic approach can improve the cognitive abilities of early childhood